Party Strategy, Candidate Selection, and Legislative Behavior in Mexico. Issue 3 (13th July 2020) - Ascencio, Sergio J.; Kerevel, Yann P.
Abstract : What explains party unity in legislatures? Prior research suggests when candidate selection and electoral rules create incentives for legislators to cultivate a personal vote, party unity should decline. However, previous theories often treat candidate selection rules as exogenous institutions that have independent effects on legislative behavior despite the fact the choice of nomination rules are often an intraparty issue and a key component of partisan electoral strategies. Here, we develop a theory linking candidate selection rules to party unity through the strategic behavior of party leaders. Our main finding is that, under personalized electoral rules, the effects of nomination rules on legislative behavior are conditional on parties' electoral incentives. We test our theory using data from the Mexican Chamber of Deputies, a case where our results are unlikely to be explained by personal vote‐seeking incentives since legislators are banned from seeking reelection.